The Participation of Tax Authorities in Insolvency Agreements - Buława, Piotr (Public Governance, Administration and Finances Law Review, 2018)
The contribution deals with a problem if and when Polish tax authorities should support insolvency agreements. Tax authorities are bodies of public law; however, they have to act within insolvency agreement proceedings as a private law subject, e.g. participate in negotiations. It creates many legal problems. The aim of the contribution is presenting possible guidelines which should allow tax authorities to make a decision if and when to support insolvency agreements. Additionally, it presents a possible amendment of the Polish law (de lege ferenta) on the basis of German experience.